Public Value Creation Through QRIS Use In Bojonegoro: A Public Service Dominant Logic Approach - Octavia, Keyka Wahyu Putri; Huda, Muhammad Miftahul; Kasiami, Sri (The Innovation of Social Studies Journal, 2026)
Digital transformation has expanded digital public services, including retail payment systems through the Quick Response Code Indonesian Standard (QRIS). Despite its rapid adoption and benefits in improving transaction efficiency and convenience, digital security risks and potential fraud may affect public trust and service sustainability. This study aims to examine perceptions of security and the process of public value creation in the use of QRIS in Bojonegoro Regency, as well as the role of institutions in ensuring the security and sustainability of QRIS as a digital public service. This study employs a qualitative approach using in-depth interviews with users, culinary merchants, regulators (Bank Indonesia), and payment service providers (PSPs). Data were thematically analyzed using the public value concept and the Public Service-Dominant Logic (PSDL) framework. The findings indicate that QRIS is positively perceived in terms of convenience and efficiency; however, perceptions of security and transaction certainty remain varied. Fraud risks and transaction failures encourage users and merchants to adopt precautionary practices, highlighting the importance of institutional responsiveness in maintaining public trust. The study demonstrates that public value in QRIS is co-created through interactions among actors, technology, and service experiences, positioning transaction security as a key factor for the sustainability of digital payment services at the local level.